1992
DOI: 10.1002/1097-0142(19920915)70:6<1462::aid-cncr2820700603>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated medullary carcinoma of the stomach

Abstract: Background. The biologic behavior of poorly differentiated medullary carcinoma of the stomach is unclear. Methods. A clinicopathologic study on 74 poorly differentiated medullary carcinomas (PMC) and 73 non‐medullary carcinomas (NMC) of the stomach was done. PMC were defined as gastric carcinomas in which more than 50% of the tumor area contained poorly differentiated adenocarcinoma with no fibrous stroma. Results. They were characterized by a location in the upper 33% of the stomach (49%), grossly expansive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
4
26
1
1
Order By: Relevance
“…This belief is based on the fact that solid carcinomas have high incidences of venous permeation and lymph node metastasis in the early phase. From a prognostic point of view, however, little is known about poorly differentiated, solid-type adenocarcinoma of the stomach (1,13). Matsusaka (9) reported that the 5-year survival rate of 67 patients with solid undifferentiated carcinoma of the stomach was only 37%.…”
Section: Discussionsupporting
confidence: 88%
“…This belief is based on the fact that solid carcinomas have high incidences of venous permeation and lymph node metastasis in the early phase. From a prognostic point of view, however, little is known about poorly differentiated, solid-type adenocarcinoma of the stomach (1,13). Matsusaka (9) reported that the 5-year survival rate of 67 patients with solid undifferentiated carcinoma of the stomach was only 37%.…”
Section: Discussionsupporting
confidence: 88%
“…This phenomenon raises the question of whether MSI-positive papillary adenocarcinoma at early stages is related to solid-type, poorly differentiated adenocarcinoma at advanced stages. Adachi et al reported that papillotubular differentiation in the mucosa of tumor margins was seen in 38 % of poorly differentiated medullary carcinomas and hypothesized that medullary-type carcinomas arise as papillary adenocarcinomas in the gastric mucosa and then become solid or medullary after tumor invasion through the gastric wall [28]. The evidence that both papillary and solid-type adenocarcinomas show similar biological behavior, such as frequent liver metastasis [28][29][30], together with our results supports this hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…Undifferentiated type tumors include histologically poorly differentiated adenocarcinoma, signet ring cell carcinoma, and mucinous adenocarcinoma, but some of these tumors show biologic behavior similar to differentiated type tumors. 4,5 The most important factors predicting outcomes of patients with gastric carcinoma are the depth of wall invasion and the status of lymph node metastasis. 6,7 Several staging systems for gastric carcinoma are based on these two parameters.…”
contrasting
confidence: 41%
“…10 In this study, we divided poorly differentiated adenocarcinoma into scirrhous type (common type) and medullary type, and we divided mucinous adenocarcinoma into well differentiated type and poorly differentiated type, according to the criteria of our previous studies. 4,5 Thus, 50 papillary adenocarcinomas, 111 well differentiated tubular adenocarcinomas, 88 moderately differentiated tubular adenocarcinomas, 29 poorly differentiated medullary adenocarcinomas, and 5 mucinous adenocarcinomas of well differentiated type were grouped into well differentiated gastric carcinoma (WGC, n ϭ 283). Also, 128 poorly differentiated scirrhous adenocarcinomas, 82 signet ring cell carcinomas, and 11 mucinous adenocarcinomas of poorly differentiated type were grouped into poorly differentiated gastric carcinoma (PGC, n ϭ 221).…”
Section: Methodsmentioning
confidence: 99%